2022
DOI: 10.1037/scp0000281
|View full text |Cite
|
Sign up to set email alerts
|

Transforming suffering through forgiveness: A religious coping approach.

Abstract: This article examines how Kenneth Pargament's theories and empirical research on religious coping informs the scientific study of forgiveness. Forgiveness can be conceptualized as a transformational religious coping approach. A comprehensive scientific understanding of forgiveness requires an examination of how various religions conceptualize and practice forgiveness, how religion can facilitate and/or impede forgiveness, and how religion can be effectively incorporated into forgiveness interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A literature survey revealed that different methods have been employed for the management of pain and inflammation for centuries. In ancient times, people believed that pain was a divine punishment ( Rye et al, 2000 ). Cupping therapy, acupuncture, or massage therapy was applied to relieve the pain ( Munir et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that different methods have been employed for the management of pain and inflammation for centuries. In ancient times, people believed that pain was a divine punishment ( Rye et al, 2000 ). Cupping therapy, acupuncture, or massage therapy was applied to relieve the pain ( Munir et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%